Chronic prostatitis: infectious or non-infectious? (experimental study) - Anatolii G. Gorbachev; Sergei Yu. Borovets; Maksim A. Rybalov; Aleksei G. Tiurin (LLC "MEDIAFORMAT", 2020)
Introduction. The pathogenesis of chronic prostatitis remains unclear. The aim of this study was to study the pathogenesis and frequency of infectious and non-infectious prostatitis and the effectiveness of prostatilen in its prevention in the experiment. Materials and methods. Experimental work was carried out on 82 male Wistar rats 5-8 months of age (weight 250-400 g). To initiate inflammation of the prostate gland, rats of the 1st and 2nd groups (30 in each) were injected into the rectum with 1 ml of a mixture of turpentine and Dimexide in a ratio of 1:4 to a depth of 2.5 cm. For rats of the 3rd group (n=17) prostatilen was intramuscularly injected daily for five days at a dose of 0.1 mg/100 g of weight. The day after the last injection into the rectum, they were also injected with a pathogenic mixture to initiate prostatitis. In the 4th group (n=5) there were control animals, which were injected intramuscularly with physiological sodium chloride solution for five days before the initiation of prostatitis. Rats were removed from the experiment by guillotinization, in the 1st group the next day, and in the 2nd group 28 days after the initiation of inflammation, and for rats of the 3rd and 4th groups - 5 days after the last injection (prostatilen or physiological solution respectively). The prostate gland and seminal vesicles were used as the test material for the culture and histological examination. Results. In the experiment, microorganisms were isolated in 23.4% of cases in the 1st group, and in 92.1% of cases in the 2nd group. Among the identified microorganisms, Staphylococcus aureus prevailed in the 1st group, and S. urealiticus in the 2nd group. The presence of mixed flora was found in 18.2% in the 1st group and in 20% in the 2nd group. During macro- and microscopic examination of the prostate gland of rats of the 3rd group, we did not find signs of its active inflammation, and during bacteriological examination, microorganisms were not detected. Conclusion. Chronic inflammation of the prostate gland initially develops as aseptic, but later the prostatitis becomes infectious. This can be confirmed by modern means and methods of laboratory diagnostics of bacterial flora in prostate exprimat in patients with chronic prostatitis. The data obtained from experimental studies confirm the ability of prostatilen to prevent the development of the inflammatory process in the prostate gland, which makes it possible to recommend it in clinical conditions for the complex therapy of patients with chronic prostatitis, as well as in means of preventing this disease.